2011
DOI: 10.1007/s00467-010-1753-1
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for children with chronic kidney disease and end-stage renal disease

Abstract: It is well known that adults suffering from chronic kidney disease (CKD) experience muscle wasting and excessive fatigue, which results in a reduced exercise capacity and muscle weakness compared to their healthy counterparts, but research suggests that this can be improved through exercise. There is very limited data available regarding exercise tolerance in children with CKD and even less on the effects of exercise training programs. However, the available evidence does suggest that like adults, children als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
0
24
0
2
Order By: Relevance
“…It has been well documented that physical inactivity in adult CKD populations is a strong predictor of cardiovascular mortality and leads to overall poor physical functioning and decreased exercise capacity [1315]. Physical activity may be a modifiable risk factor for CVD in this population, and new research suggests exercise should be prescribed as part of the CKD treatment regimen [1623].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well documented that physical inactivity in adult CKD populations is a strong predictor of cardiovascular mortality and leads to overall poor physical functioning and decreased exercise capacity [1315]. Physical activity may be a modifiable risk factor for CVD in this population, and new research suggests exercise should be prescribed as part of the CKD treatment regimen [1623].…”
Section: Introductionmentioning
confidence: 99%
“…Children and adolescents with advanced CKD have been found to have significant deficits in lean leg mass, indicative of skeletal muscle wasting, and a recent study demonstrated decreased muscle quality in children with CKD stages 2-5D, with significantly lower muscle torque relative to muscle cross-sectional area compared to controls [34, 35]. The current body of literature regarding physical activity in children with CKD has focused on the ESKD population rather than the early stages of CKD and also suggests that physical activity may be a modifiable risk factor for later CVD mortality in adulthood [13, 3641]. The burden of inactivity is largely unknown in the pediatric CKD population and could provide a point of intervention early in the disease course to prevent future morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that CKD leads to reduced physical activity and an increased risk of cardiovascular disease (CVD) [2], [3]. A sedentary lifestyle increases the risk of CVD, but CVD can be ameliorated by physical fitness [3], [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic exercise has been shown to improve renal and cardiac function in individuals with CKD [6] and in overweight rats with metabolic and cardiac dysfunction [7], and exercise has gained more attention as a possible tool for preventing, reducing or delaying CKD progression [3], [4], [5], [6], [7]. It has been suggested that appropriate exercise may improve a patient's physical strength and quality of life [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, there was good adherence to wearing the pedometers and reporting the step counts, with three-quarters of the participants providing data for all twelve weeks of the study. The “disconnect” between adherence to wearing the pedometers and lack of adherence to the recommended increases in physical activity suggests that our intervention was not sufficient to motivate children and adolescents with CKD to increase their physical activity, a problem that was also encountered in prior studies of exercise in this population [19,20,22]. Indeed, lack of time and being too tired were the top two barriers cited by participants in our study, particularly among teenagers who worked.…”
Section: Discussionmentioning
confidence: 99%